2008
DOI: 10.1093/jac/dkn022
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal susceptibility profile of clinical Fusarium spp. isolates identified by molecular methods

Abstract: Six different species were identified. Fusarium solani was the most frequently isolated, followed by Fusarium oxysporum, Fusarium proliferatum and Fusarium verticilloides. Amphotericin B was the only drug with in vitro activity (range: 0.015-32 mg/L). The rest of the antifungals tested (itraconazole, voriconazole, ravuconazole, posaconazole and terbinafine) showed very poor activity against Fusarium, confirming the multiresistant nature of this genus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
110
4
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(143 citation statements)
references
References 28 publications
(17 reference statements)
15
110
4
11
Order By: Relevance
“…Consistent with the findings of others (1,2,24), the six antifungal agents tested in the present study showed poor overall in vitro activities against 20 phylogenetically diverse species. The most significant finding is that AMB was the most active drug against all Fusarium species, including the FSSC, as has been reported by others (2,24); however, AMB MICs varied with species, and MICs against the FIESC were Ͼ8 g/ml (Table 1).…”
Section: Vol 49 2011 Seven-locus Sequence Analysis Of Fusarium 1895supporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with the findings of others (1,2,24), the six antifungal agents tested in the present study showed poor overall in vitro activities against 20 phylogenetically diverse species. The most significant finding is that AMB was the most active drug against all Fusarium species, including the FSSC, as has been reported by others (2,24); however, AMB MICs varied with species, and MICs against the FIESC were Ͼ8 g/ml (Table 1).…”
Section: Vol 49 2011 Seven-locus Sequence Analysis Of Fusarium 1895supporting
confidence: 90%
“…In humans, they cause infections ranging from superficial disease (e.g., keratitis and onychomycosis) to life-threatening disseminated infections; the latter occur predominantly in severely immunocompromised patients (7,18,19) in whom mortality approaches 100% (10). This high mortality is due in part to frequent delays in diagnosis and to the fact that most Fusarium species, particularly those nested within the Fusarium solani species complex (FSSC), are typically resistant to most antifungal agents (1,2,28).…”
mentioning
confidence: 99%
“…are of relative resistance to most antifungal agents (54). Among the small number of isolates in the present study, MICs were generally Յ4 g/ml for both posaconazole and voriconazole against the 10 Fusarium isolates tested: G. fujikuroi (80% Յ4 g/ml) (Table 6), F. solani (67%) (see the supplemental material), and Fusarium spp.…”
Section: Different Laboratories (2003 To 2007 At the University Of Iomentioning
confidence: 64%
“…While refractory onychomycoses are not life-threatening, timely and effective treatment for deep and disseminated fusariosis is very important. Joint guidelines on the treatment of hyalohyphomycoses recommend amphotericin B and voriconazole for the treatment of systemic fusariosis [18], despite variable minimum inhibitory concentration (MIC) test results for both drugs [2,16,17,19]. Hence, accurate identification of the species involved is of importance for epidemiological studies and for guiding clinical follow-up of the patients [2,13].…”
Section: Introductionmentioning
confidence: 99%